The use of vegetation by bird communities in Menjangan Island, West Bali National Park - Abimanyu, Anak Agung Ngurah Bagus; Wijaya, I Made Saka; Sukrasena, I Gede; Yuni, Luh Putu Eswaryanti Kusuma (Jurnal Biologi Udayana; Vol 28 No 2 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i02.p06, 2025)
Menjangan Island is located in the West Bali National Park area which has a rich variety of flora and fauna. The ecosystem on Menjangan Island consists of several habitat types, namely savanna, coastal forest and lowland monsoon forest, which are habitats for bird communities. However, human activity in several places has the potential to cause disruption to the habitat of bird communities. The aim of this research was to analyze the use of vegetation by bird communities on Menjangan Island, West Bali National Park. The method for collecting data on bird species was carried out using the point count method with a radius of 50 m in the morning, afternoon and evening. Recording the plant species used by birds was also carried out. Observations were carried out from December 2023 to January 2024, in three types of habitat with three observation points in each habitat. There were 40 bird species from 29 families found during observations that utilized various vegetation. In general, bird species richness in natural habitats was higher than in anthropogenic habitats. During observations, a total of 40 bird species from 29 families were found utilizing various vegetation. Pilang ( Vachellia leucocephala ) was the most used vegetation by bird species. A total of 29 bird species from 21 families were observed using it.